2023
DOI: 10.1021/acs.estlett.3c00282
|View full text |Cite
|
Sign up to set email alerts
|

Functional Group Properties and Position Drive Differences in Xenobiotic Plant Uptake Rates, but Metabolism Shares a Similar Pathway

Claire P. Muerdter,
Megan M. Powers,
Danielle T. Webb
et al.

Abstract: Plant uptake of xenobiotic compounds is crucial for phytoremediation (including green stormwater infrastructure) and exposure potential during crop irrigation with recycled water. Experimentally determining the plant uptake for every relevant chemical is impractical; therefore, illuminating the role of specific functional groups on the uptake of trace organic contaminants is needed to enhance predictive power. We used benzimidazole derivatives to probe the impact of functional group electrostatic properties an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…The rapid absorption equilibrium and the satisfactory fit result with the one compartment model implied that uptake to root epidermis might be the main absorption mechanism to guvermectin, and apoplastic absorption pathway was the other mechanism . The rapid plant uptake may result from two strongly electron-withdrawing groups (amino group electronegativity = 2.42 Pauling units, hydroxy group electronegativity = 2.68 Pauling units). , …”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The rapid absorption equilibrium and the satisfactory fit result with the one compartment model implied that uptake to root epidermis might be the main absorption mechanism to guvermectin, and apoplastic absorption pathway was the other mechanism . The rapid plant uptake may result from two strongly electron-withdrawing groups (amino group electronegativity = 2.42 Pauling units, hydroxy group electronegativity = 2.68 Pauling units). , …”
Section: Resultsmentioning
confidence: 90%
“…30 The rapid plant uptake may result from two strongly electron-withdrawing groups (amino group electronegativity = 2.42 Pauling units, hydroxy group electronegativity = 2.68 Pauling units). 36,37 The absorption and accumulation of guvermectin in the crop roots and shoots were distinctly dependent upon the crop categories. At uptake equilibrium stage, guvermectin had a much higher accumulation in the root of lettuce, with average guvermectin concentrations of 1.87-and 3.04-fold for the root of rice and carrot, respectively (Figure 1a).…”
Section: Uptake Kinetic Of Guvermectin In Root Andmentioning
confidence: 99%
“…Knowledge concerning the plant uptake, translocation, and metabolism is vital in understanding the risks of organic chemicals and promoting efficient phytoremediation efforts . This study demonstrated that phloem translocation and plant excretion were important pathways to transport phenamacril from shoots to roots and rhizosphere environments, resulting in a prolonged cycling contamination, which should be considered in developing more accurate prediction models for assessing the risks of phloem-transported chemicals to ecosystems. After being taken up, phenamacril was extensively transformed (e.g., 76.4%) in plants, with nine metabolites newly identified.…”
Section: Resultsmentioning
confidence: 92%
“…Plant uptake and translocation of pesticides are closely related to their physiochemical properties such as hydrophobicity, molecular weight, chemical speciation (e.g., ionizable pesticides), electrostatic properties, and positions of molecular functional groups, as well as plant properties . The exact uptake pathways and in-plant distribution processes are essential knowledge in developing models to predict plant uptake and accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…This variability is unsurprising since the detection frequencies of both tire-derived compounds and pharmaceuticals in wastewater and surface water bodies also varies highly from compound to compound, due to differences in emissions and environmental stability (38,(62)(63)(64)(65)(66). In the agricultural environment, soil sorption, microbial transformation, extent of plant uptake and translocation, and plant metabolism vary greatly for compounds with different chemical structures (6,50,51,54,(67)(68)(69)(70).…”
Section: Discussionmentioning
confidence: 99%